Natural Antimicrobials and Antioxidants Added to Polylactic Acid Packaging Films. Part I: Polymer Processing Techniques - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Lopez de Dicastillo-Bergamo, A; Patiño-Vidal, C; Velasquez, E (Blackwell Publishing Inc., 2021)
Currently, reducing packaging plastic waste and food losses are concerning topics in the food packaging industry. As an alternative for these challenges, antimicrobial and antioxidant materials have been developed by incorporating active agents (AAs) into biodegradable polymers to extend the food shelf life. In this context, developing biodegradable active materials based on polylactic acid (PLA) and natural compounds are a great alternative to maintain food safety and non-toxicity of the packaging. AAs, such as essential oils and polyphenols, have been added mainly as antimicrobial and antioxidant natural compounds in PLA packaging. In this review, current techniques used to develop active PLA packaging films were described in order to critically compare their feasibility, advantages, limitations, and relevant processing aspects. The analysis was focused on the processing conditions, such as operation variables and stages, and factors related to the AAs, such as their concentrations, weight losses during processing, and incorporation technique, among others. Recent developments of active PLA-based monolayers and bi- or multilayer films were also considered. In addition, patents on inventions and technologies on active PLA-based films for food packaging were reviewed. This review highlights that the selection of the processing technique and conditions to obtain active PLA depends on the type of the AA regarding its volatility, solubility, and thermosensitivity. © 2021 Institute of Food Technologists®.